Paradigma Tafaqquh Fiddin Perspektif Imam syafi’i dan Implikasinya dalam Merawat Tradisi Keilmuan Pendidikan Islam - Hidayat, Rahmat; AK, Warul Walidin; Silahuddin, Silahuddin (Sekolah Tinggi Agam Islam Sumatera Medan, 2023)
In modern times the level of religiousness of society tends to weaken along with their focus and needs of the world. As evidence, some modern people who are less wise do not make religion a solution in their lives. Some other people are actually religious, but their understanding is only limited to the implementation of worship. In this regard, this study aims to analyze the paradigm of Tafaqquh Fiddin from Imam Syafi'i's perspective and its implications for the scientific tradition of Islamic education. This research uses a qualitative method with a library research approach. The main source of this research is the book of Al-Umm and Ar-Risalah by Imam Syafi'i, supporting sources of research articles. The results revealed that the paradigm of tafaqquh fiddin includes the obligation to study religious knowledge, the importance of maintaining and cleaning oneself from acts prohibited by religion and having good morals, choosing the right teacher who has a scientific sanad, learning in depth, being flexible in religion with the correct legal basis, teaching and practicing knowledge, and studying knowledge for the sake of Allah. Scholarly Tradition in Islamic education requires complexity in demanding knowledge, not only in terms of material, but also in terms of how to get it.